2021
DOI: 10.1186/s12936-021-03708-z
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance profile and clonality of Plasmodium falciparum parasites in Cape Verde: the 2017 malaria outbreak

Abstract: Background Cape Verde is an archipelago located off the West African coast and is in a pre-elimination phase of malaria control. Since 2010, fewer than 20 Plasmodium falciparum malaria cases have been reported annually, except in 2017, when an outbreak in Praia before the rainy season led to 423 autochthonous cases. It is important to understand the genetic diversity of circulating P. falciparum to inform on drug resistance, potential transmission networks and sources of infection, including pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…However, the Island still records a few cases of indigenous infections and imported cases, mostly originating from neighboring African countries. The country aimed at eliminating malaria by 2020 but experienced an epidemic in 2017 however; its last local case was in January 2018 (DePina et al 2020 ; Da Veiga Leal et al 2021 ) and has currently applied for malaria elimination status (WHO 2021a , b , c ). As part of its strategic plan to attain elimination, the country ensured that quality-assured diagnoses were done in all health facilities and, as such become the main source of passives cases following, which confirmed cases are reported within 24 h and hospitalized for treatment (WHO 2021a , b , c ).…”
Section: Diagnostic Approach and Challenges In Different Malaria Regionsmentioning
confidence: 99%
“…However, the Island still records a few cases of indigenous infections and imported cases, mostly originating from neighboring African countries. The country aimed at eliminating malaria by 2020 but experienced an epidemic in 2017 however; its last local case was in January 2018 (DePina et al 2020 ; Da Veiga Leal et al 2021 ) and has currently applied for malaria elimination status (WHO 2021a , b , c ). As part of its strategic plan to attain elimination, the country ensured that quality-assured diagnoses were done in all health facilities and, as such become the main source of passives cases following, which confirmed cases are reported within 24 h and hospitalized for treatment (WHO 2021a , b , c ).…”
Section: Diagnostic Approach and Challenges In Different Malaria Regionsmentioning
confidence: 99%
“…The genetic diversity of Plasmodium spp. has been related to the ability of parasites to adapt adequately to their hosts through the selection of advantageous traits, such as antigenic variability that allows them to evade the immune response, as well as the emergence of mutations responsible for resistance to antimalarials [3][4][5][6][7]. Genetically diverse populations of Plasmodium are common in regions with high transmission patterns, such as sub-Saharan Africa and some Southeast Asian countries [8][9][10][11][12], but as the incidence of malaria declines, the parasite's genetic diversity is expected to decline as well [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Our data is similar to data from the study carried out in Cape Verde, which showed that of the 131 patients and 137 close contacts followed, malaria was predominantly alone (73.3%), in male (65.6%), and younger than cases not associated with malaria ( P < .001), students and tertiary sector activities accounted for 80.2% of malaria cases and multiple logistic regression models suggested an increased risk of malaria because of gender male (OR = 4.99; 95% CI 2.90-8.58) and single (OR = 1.92, 95% CI 1.02-3.58), with potential risk in older age (OR = 0.98; 95%CI 0.97-1.00). 17 …”
Section: Discussionmentioning
confidence: 99%
“…Our data is similar to data from the study carried out in Cape Verde, which showed that of the 131 patients and 137 close contacts followed, malaria was predominantly alone (73.3%), in male (65.6%), and younger than cases not associated with malaria (P < .001), students and tertiary sector activities accounted for 80.2% of malaria cases and multiple logistic regression models suggested an increased risk of malaria because of gender male (OR = 4.99; 95% CI 2.90-8.58) and single (OR = 1.92, 95% CI 1.02-3.58), with potential risk in older age (OR = 0.98; 95%CI 0.97-1.00). 17 When evaluating how pharmacological procedures were related to resistance to malaria treatment, it was observed that although almost all patients received antimalarial treatment, especially Artemether, that the use of certain drugs from other groups, with antibiotics, antipyretics, and others, when combined with antimalarial treatment, may increase or reduce the possibility of resistance (Table 2). Our data do not show associations between artemether-lumefantrine and artesunateamodiaquine, which seems to be more effective drugs due to their mechanism of action and therefore have been proposed as alternatives in the treatment of parasites drug-resistant.…”
Section: Discussionmentioning
confidence: 99%